CHEMICAL, TOXICOLOGICAL, ANTI-INFLAMMATORY AND ANTIMICROBIAL EVALUATION OF GANODERMA LUCIDUM EXTRACTS. - Wadt, Nilsa Sumie Yamashita; Okamoto, Marise K. H.; Hi, Edgar Matias Bach; Bach, Erna Elisabeth (Emirates Journal of Food and Agriculture, 2015)
Ganoderma lucidum (Fr.) Krast, a basidiomycete belonging to the Ganodermataceae family is one of the most famous traditional Chinese medicinal herbs, used as a healthy food and in medicine. In Brazil, some people produced also in the same process and is indicated that is a nutriceutical product. The dry Ganoderma lucidum of three different states of Brazil were milled and extracted with hot water, water and ethanol, and ethanol only. The results obtained demonstrated that extracts with HotWater and Water-ethanolic presented more concentration of beta-glucan and proteins. Extract ethanolic presents higher concentration of free sugar and increased concentration of phenols when compared with others extracts but doesn’t have protein. When make a mixture of water extract with alcohol, there is a higher concentration of beta-glucan with protein and phenol. When compared samples from three states, the one from Brasília presented more beta-glucan, phenols, proteins and free sugar in all extractions. The hydroethanolic extract showed tannins, flavonoids, terpens, steroid nucleus. It showed an anti-inflammatory and antimicrobial activity when tested with specific reaction for each group. It showed an anti-inflammatory activity when tested by cotton pellets implantation in rats and antimicrobial activity in pour plate assay for Staphylococcus aureus and Candida albicans. It did not exhibit acute toxicology in acute model in mouse.